Analisis dan Evaluasi Intensitas Kebisingan Area Kerja pada Produksi Gabion dengan Golden Software Surfer 25 (Studi Kasus : PT. Perusahaan Kawat Baja) - Putro, Mahardhika Suryo Wibowo; Murnawan, Hery; Rosyidiin, Afrigh Fajar (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Perusahaan Kawat Baja (PT. PKB) is a manufacturing industry producing steel wire ropes, stranded wires, gabions, and other steel wire products. Third-party monitoring in May 2023 found noise intensity exceeding the Threshold Limit Value (TLV) at measurement points, with maximum exposure of 85 dB over an 8-hour workday. This study aims to evaluate noise exposure levels in the gabion production area. Research methods included noise mapping using Golden Software Surfer 25 on a 2 x 2 meter scale, HIRARC (High Risk Assessment and Risk Control) for risk management, and Benefit Cost Analysis (BCA) to assess the feasibility of noise control measures. Findings revealed 147 measurement points exceeding 85 dB. PT. PKB implemented noise control through engineering, administrative measures, and Personal Protective Equipment. A B/C Ratio of 3.57 indicated the economic viability of these risk control measures.